A Challenge to Conventional Fish Meal: Effects of Soy Protein Peptides on Growth, Histomorphology, Lipid Metabolism and Intestinal Health for Juvenile Pompano Trachinotus ovatus - Lin, Huaxing; Tan, Beiping; Ray, Gyan Watson; Zeng, Min; Li, Mei; Chi, Shuyan; Yang, Qihui (Frontiers in Marine Science, 2022)
This experiment was conducted to assess the possibility of replacing fishmeal (FM) with soy protein peptide (SPP) at different levels—FM (0%), S5 (5.45%), S10 (10.90%), S20 (21.78%), S25 (27.23%)—and its effects on growth, immuno-enzymatic activities, histology, gene expression related to liver lipid metabolism and intestinal immunity in juvenile pompano Trachinotus ovatus (Initial mean weight = 39.88 ± 0.15 g). 800 healthy and uniformed-size fish were distributed to five groups of four replicates, each with 40 fish in each floating cage and fed twice daily for 8 weeks. Results showed that there was no significant difference in the growth of Trachinotus ovatus by replacing FM with SPP (P > 0.05). The glutathione peroxidase (GSH-Px) activity in serum in the S10 group was significantly higher than in the FM group, and the malondialdehyde (MDA) content in serum showed a significant decrease (P < 0.05). SPP significantly improved intestinal immunity by increasing alkaline phosphatase (AKP), lysozyme (LYZ) activities and up-regulating interleukin 10 (IL-10), complement 4 (C4) mRNA levels, while simultaneously decreasing triglyceride (TG), total cholesterol (T-CHO) contents and down-regulating interleukin-1β (IL-1β) mRNA expression. Villus length (VL) and muscle thickness (MT) in the S10 group were significantly higher than those in the FM group (P < 0.05). SPP significantly improved liver fat metabolism via increasing carnitine palmitoyl transferase Ι (CPTΙ) mRNA levels, but by decreasing triglyceride (TG), total cholesterol (T-CHO) content and down-regulating fatty acid synthesis (FASN) mRNA expression (P < 0.05). In summary, the replacement of FM with SPP had a beneficial effect on the intestinal and liver health for juvenile pompano Trachinotus ovatus by promoting intestinal growth and lipid metabolism, improving immunity, and reducing liver fat accumulation without affecting growth performance.